KELAS LITERASI KREATIF: GERAKAN MEMBACA DAN MENULIS - Esti Perwitasari; jatiningsih, Oksiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low students’ interest in reading and writing remains one of the educational challenges commonly found in society. This condition is influenced by the limited availability of creative learning spaces, the lack of community-based literacy activities, and students’ low involvement in reading and writing practices outside the school environment. Based on these conditions, this community service research aims to develop the program entitled “Creative Literacy Class: A Community-Based Reading and Writing Movement for Students” as an effort to increase students’ participation in literacy activities through an active and enjoyable community approach. This study employed a descriptive qualitative approach within the framework of community service activities. The participants involved elementary and junior high school students, program facilitators, and local community members participating in the literacy program. Data were collected through observation, interviews, documentation, and field notes. Literacy activities were implemented through shared reading sessions, story discussions, creative writing practices, educational games, and the publication of students’ written works. The findings indicate that the Creative Literacy Class program successfully increased students’ engagement in reading and writing activities. Students became more active, confident, and creative in expressing their ideas through writing and group discussions. In addition, community-based activities created a more human-centered, collaborative, and enjoyable learning environment, allowing literacy culture to gradually develop within the community. The program also strengthened social relationships among students, facilitators, and community members in supporting collaborative learning activities. Based on these findings, it can be concluded that the “Creative Literacy Class: A Community-Based Reading and Writing Movement for Students” program serves as an effective alternative for strengthening literacy culture through a participatory, creative, and sustainable community approach.